Match the New Product Development project with Its Context - Eko Agus Prasetio (ITB, 2012)
This paper provides the frameworks and tools for matching the innovation and new product development project with its context in a European plastics converting company which develops, manufactures and markets total pipe systems. Where the company moves into new segment, it applies its conventional internally-oriented approach to its innovation and new product development and as a consequence, it faces probelms in terms of delay oftime to market and incrasing costs. The development of composite manifold is taken as an illustrative case of the problem that the company is facing. As indicated by the case, the company is trapped in a"one-size-fits-all" approach in its innovation and new product development process. The paper is developed through the use of primary research in the form of in-depth interview and case-study discussions with innovation managers, program managers and marketing managers in the company's headquarters (Netherlands) and other European countries, and secondary research in the form of company data analysis and extensive literature review. Frameworks of newness and risk map as well as the corresponding scoring system is elaborated and developed to increase the efficiency and effectiveness in the comapny's NPD